Prevalence of HIV and Syphilis Infection among Men Who Have Sex with Men in China: A Meta-Analysis. (23rd April 2014) - Zhou, Yunhua; Li, Dongliang; Lu, Dabing; Ruan, Yuhua; Qi, Xiao; Gao, Ge
Abstract : Objectives . To figure out the most current prevalence of HIV and syphilis in MSM in China. Methods. A meta-analysis was conducted on the studies searched through PubMed, CNKI, and Wanfang published between 1 January 2009 and 11 April 2013. Results. Eighty-four eligible studies, either in Chinese or in English, were included in this review. The pooled prevalence of HIV and syphilis infection in MSM in China was 6.5% and 11.2%, respectively. The subgroup analyses indicated that the prevalence of HIV infection was higher in the economically less developed cities than that in the developed cities (7.5% versus 6.1%, P < 0.05 ). In contrast, the prevalence of syphilis infection was lower in less developed cities than in developed cities (8.6% versus 15.1%). Studies with a sample size smaller than 500 had a lower prevalence of HIV and syphilis infection than those with a sample size greater than 500 (5.9% versus 7.2% for HIV; 11.0% versus 11.5% for syphilis, respectively). Conclusions. HIV and syphilis infection are prevalent in MSM in China. The different prevalence of HIV and syphilis infection between developing and developed cities underscores the need to target prevention strategies based on economic conditions.